Persepsi Mahasiswa Tentang Pembelajaran Melalui Media Sosial Whatsapp - Nyimas Tammara Andini; Eni Murdiati; Manalullaili Manalullaili (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This study discusses "Student Perceptions About Learning Through Whatsapp Social Media" with the problems in this study are: What are the perceptions of various students about learning through whatsapp social media because along with the times, the presence of the internet provides information for the general public including students. With the emergence of social media which is used as a medium for communication, it allows everyone to interact with people who are far away without knowing boundaries and time. From various backgrounds and ages, almost all have and use social media. The purpose of this research is to find out. The purpose of this research is to find out what students can learn through whatsapp social media about where students know a lot to get information, communicate more easily, motivation in learning which can increase student enthusiasm. In this study, the authors used qualitative research with data sources obtained through observation, interviews and documentation. After that the data obtained is analyzed, presenting the data, and making conclusions. Based on the research results that have been obtained from learning through whatsapp social media can continue learning discussions, facilitate assignment collection, organize learning materials, create learning communities, get information quickly, practically, do learning easily, anywhere, facilitate communication among students and add outlook.